2014
DOI: 10.1111/bjh.12832
|View full text |Cite
|
Sign up to set email alerts
|

Impaired proplatelet formation in immune thrombocytopenia: a novel mechanism contributing to decreased platelet count

Abstract: Summary The pathophysiological mechanisms contributing to the decreased platelet count in immune thrombocytopenia (ITP) are not entirely understood. Here, we investigated the key step of proplatelet formation (PPF) by studying the effect of ITP plasma in thrombopoiesis. Normal cord blood‐derived mature megakaryocytes were cultured in the presence of recalcified plasma from ITP patients, and PPF was evaluated by microscopic analysis. Patient samples induced a dose‐dependent inhibition in PPF, as well as decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 23 publications
4
47
0
Order By: Relevance
“…47 The differences between our and previous [8][9][10]47 reports regarding MK numbers and maturation may be related to the following factors: (i) our treatments with ITP sera and IgG were carried out in cultures containing already differentiating MK, i.e. cultures with over 50% CD41 + cells; (ii) even though most of our patients had similar specificities of antiplatelet autoantiobodies to those previously reported, their target epitope/subunit, titer and avidity could be different; (iii) the subjects in the study by Chang et al mostly had acute childhood ITP 9 and the pathophysiology of this condition may be somewhat different from that of chronic adulthood ITP.…”
mentioning
confidence: 99%
“…47 The differences between our and previous [8][9][10]47 reports regarding MK numbers and maturation may be related to the following factors: (i) our treatments with ITP sera and IgG were carried out in cultures containing already differentiating MK, i.e. cultures with over 50% CD41 + cells; (ii) even though most of our patients had similar specificities of antiplatelet autoantiobodies to those previously reported, their target epitope/subunit, titer and avidity could be different; (iii) the subjects in the study by Chang et al mostly had acute childhood ITP 9 and the pathophysiology of this condition may be somewhat different from that of chronic adulthood ITP.…”
mentioning
confidence: 99%
“…3). The investigation provides additional evidence that hindrance of the final stages of MK differentiation by autoantibodies contributes to immunopathological mechanisms of ITP32. Two previous studies showed that anti-platelet autoantibodies isolated from chronic ITP patients perturbed MK polyploidy apart from MK maturation3031.…”
Section: Discussionmentioning
confidence: 66%
“…The impaired megakaryocytopoiesis and platelet production in ITP pathogenesis have been demonstrated in several animal models and MK morphologic studies2728. In vitro cell culture studies have shown that plasma of ITP patients hinders MK differentiation293031 and in some instances also inhibits proplatelet formation32 because the plasma contains autoantibodies directed at platelets. Similarly, we found that anti-CD41 antibody hampered MK differentiation, proplatelet formation, and platelet generation in a dose-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The impaired megakaryocytopoiesis and platelet production in ITP pathogenesis have been demonstrated in several animal models and MK morphologic studies 27,28 . In vitro cell culture studies have shown that plasma of ITP patients hinders MK differentiation [29][30][31] and in some instances also inhibits proplatelet formation 32 because the plasma contains autoantibodies directed at platelets. Similarly, we found that anti-CD41 antibody hampered MK differentiation, proplatelet formation, and platelet generation in a dose-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 99%